A role for the epithelial-cell-specific tyrosine kinase Sik during keratinocyte differentiation - Vasioukhin, Valeri (The National Academy of Sciences of the USA, 1997)
Sik, the mouse homologue of the breast tumor kinase Brk, is expressed in differentiating cells of the gastrointestinal tract and skin. We examined expression and activity of Sik in primary mouse keratinocytes and a mouse embryonic keratinocyte cell line (EMK). Calcium-induced differentiation of these cells has been shown to be accompanied by the activation of tyrosine kinases and rapid phosphorylation of a 65-kDa GTPase-activating protein (GAP)-associated protein (GAP-A.p65). We demonstrate that Sik is activated within 2 min after calcium addition in primary keratinocytes and EMK cells. In EMK cells, Sik binds GAP-A.p65, and this interaction is mediated by the Sik Src homology 2 domain. Although Sik directly complexes with GAP-A.p65, overexpression of wild-type or kinase defective Sik in EMK cells does not lead to detectable changes in GAP-A.p65 phosphorylation. These data suggest that Sik is not responsible for phosphorylation of GAP-A.p65. GAP-A.p65 may act as an adapter protein, bringing Sik into proximity of an unidentified substrate. Overexpression of Sik in EMK cells results in increased expression of filaggrin during differentiation, supporting a role for Sik in differentiation.